Pengangkatan Rahasia (Secret Rapture): Analisis Teologi Alkitabiah - Refamati Gulo Chailys (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2023)
This research is an in-depth study aimed at analyzing the concept of the Secret Rapture from a theological perspective within the context of the Bible. The Secret Rapture is one of the debated topics in Christian theology, relating to views about when and how the rapture of believers will occur before the period of tribulation or the end times. In this study, a biblical approach is used to investigate key aspects of the Secret Rapture as presented in the Bible. First, the research will review relevant Bible texts to identify the theological foundations underlying the Secret Rapture. Furthermore, the interpretation of Bible prophecies about the end times, particularly in the Book of Revelation, will be examined to understand how the rapture is understood by prominent theologians. Moreover, this paper will also discuss different theological perspectives on the Secret Rapture and the arguments that underlie each viewpoint. Some theologians may view the Secret Rapture as a distinct event separate from the tribulation period, while others may see it as part of a sequence of events occurring during the end times. This research employs a literature review method, which involves gathering data from various sources, examining and analyzing the data to obtain information about the researched topic. Through literature-based research, accurate facts can be discovered. Please note that the translation provided is generated by AI and may require further review by a fluent English speaker to ensure its accuracy and coherence. The results of this analysis are expected to provide a deeper understanding of the theological significance of the Secret Rapture within the biblical context. Moreover, it is hoped that this journal will contribute to a broader theological discourse on this topic, helping to enlighten and enrich the understanding of Christian believers regarding their hope for the future. Penelitian ini bertujuan untuk menganalisis konsep Pengangkatan Rahasia (Secret Rapture) dari sudut pandang teologi dalam konteks Alkitabiah. Pengangkatan Rahasia ialah salah satu topik yang mendebatkan di dalam teologi Kristen, yang berkaitan dengan pandangan tentang kapan serta bagaimana pengangkatan orang percaya akan terjadi sebelum masa kesengsaraan atau akhir zaman. Dalam penelitian ini, pendekatan alkitabiah digunakan untuk menyelidiki aspek-aspek kunci dari Pengangkatan Rahasia seperti yang terdapat dalam Alkitab. Pertama, penelitian ini akan meninjau teks-teks Alkitab yang relevan untuk mengidentifikasi dasar-dasar teologi yang mendasari Pengangkatan Rahasia. Selanjutnya, penafsiran nubuat-nubuat Alkitab tentang akhir zaman, khususnya kitab Wahyu, akan diuji untuk melihat bagaimana pengangkatan tersebut dipahami oleh beberapa ahli teologi terkemuka. Selain itu, penelitian ini juga akan membahas perspektif teologis berbeda mengenai Pengangkatan Rahasia dan argumen-argumen yang mendasari masing-masing pandangan. Beberapa teolog mungkin memandang Pengangkatan Rahasia sebagai peristiwa yang nyata dan terpisah dari periode kesengsaraan, sementara yang lain mungkin melihatnya sebagai bagian dari suatu rangkaian peristiwa yang terjadi selama masamasa akhir zaman. Dengan menggunakan metode penelitian ini didasarkan pada penelitian kepustakaan yaitu mengumpulkan data dari literatur-literatur, menelaahnya dan menganalisis data tersebut untuk mendapatkan informasi-informasi mengenai topik yang diteliti. Melalui penelitian secara kepustakaan dapat menemukan fakta secara tepat. Hasil dari analisis ini diharapkan bisa memberi pemahaman yang mendalam tentang signifikansi teologis Pengangkatan Rahasia dalam konteks Alkitabiah. Selain itu, diharapkan pula jika jurnal ini akan menyumbang pada dialog teologis yang lebih luas mengenai topik ini, membantu mencerahkan serta memperkaya pemahaman umat Kristen tentang harapan mereka pada masa yang akan datang.